Wireless Technology Development: History, Now, and Then - Dewi, Lusiana Citra (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Wireless technology is one of many technologies that can enable people to communicate with each other by air medium, or rather you can say by radio frequency. This paper discusses about history of wireless technology, different kinds of wireless connection, wireless technology standards, and a few comparisons of different kinds of world’s wireless technology standards. Besides discussing about history about wireless technology and wireless technology that we can use nowadays, this paper also reviews about prediction of wireless technology development in the future for better human life. The purpose of this study is to give a glimpse of view on how the wireless technology develops, the world standard for wireless technologies and work system, the security and characteristic for each wireless technology including advantages and drawbacks, and future wireless technology development.